Loading Rate Effect of Rock Material with the Direct Tensile and Three Brazilian Disc Tests - Fengqiang Gong; Le Zhang; Shanyong Wang (Advances in Civil Engineering)
A series of experimental tests were conducted to investigate the effects of loading rate on the tensile strength of sandstone by using four test methods, including a direct tensile method and three typical Brazilian disc methods (plate loading, circular arc loading, and strip loading). The loading rates used in these tests varied from 10−2 MPa/s to 100 MPa/s. The results show that the rate effects are clear for these test methods, and the tensile strength of sandstone will increase linearly with the logarithm of the loading rate. At the same loading rate, it is found that the tensile strengths of the sandstone specimens under plate loading and arc loading are relatively similar and are much greater than the direct tensile strength, while the tensile strength under strip loading is less than the direct strength. A comprehensive comparison suggested that the strip loading method can be adopted for the Brazilian disc test, while the obtained strength should be modified with a coefficient of 1.37 to obtain the direct tensile strength.